2022
DOI: 10.1128/jvi.01600-21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of B Cell Receptor Repertoires Reveals Key Signatures of the Systemic B Cell Response after SARS-CoV-2 Infection

Abstract: A comprehensive study of the B cell response against SARS-CoV-2 could be significant for understanding the immune response and developing therapeutical antibodies and vaccines. To define the dynamics and characteristics of the antibody repertoire following SARS-CoV-2 infection, we analyzed the mRNA transcripts of immunoglobulin heavy chain (IgH) repertoires of 24 peripheral blood samples collected between 3 and 111 days after symptom onset from 10 COVID-19 patients. Massive clonal expansion of naïve B cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 94 publications
(80 reference statements)
0
38
0
Order By: Relevance
“…The hypothesis that recurrent substitutions at 452 is related to evasion of R1-32 like antibodies suggested that R1-32 like antibodies may be common within the population. We searched immunoglobulin heavy chain (IgH) repertoires of 20 COVID-19 patients and 25 healthy donors (Niu et al, 2020;Yan et al, 2021;Zhang et al, 2021b), for VH1-69 transcripts having at least 80% amino acid homology and looking for GYSGYG/D motif in HCDR3 (Fig. 4f).…”
Section: R1-32 Like Antibodies Represents a Population Antibody Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that recurrent substitutions at 452 is related to evasion of R1-32 like antibodies suggested that R1-32 like antibodies may be common within the population. We searched immunoglobulin heavy chain (IgH) repertoires of 20 COVID-19 patients and 25 healthy donors (Niu et al, 2020;Yan et al, 2021;Zhang et al, 2021b), for VH1-69 transcripts having at least 80% amino acid homology and looking for GYSGYG/D motif in HCDR3 (Fig. 4f).…”
Section: R1-32 Like Antibodies Represents a Population Antibody Responsementioning
confidence: 99%
“…To determine the prevalence of R1-32 like antibodies, we analyzed nearly 2 billion IgH sequences from 3 datasets that described previously (Niu et al, 2020;Yan et al, 2021;Zhang et al, 2021b). Germline gene usage was determined using MIXCR v3.0.3 (Bolotin et al, 2015), and IGHV1-69-encoded IgH sequences were extracted for downstream analysis.…”
Section: Analysis Of Ighv1-69-encoded Igh Sequences and R1-32 Like Se...mentioning
confidence: 99%
“…It has been widely reported that SARS-CoV-2 infections elicit germline like antibodies with low SHM rates, indicating an acute activation of naïve B cells. These studies were mostly based on non-vaccinated COVID-19 patients infected in initial stages of the pandemic [4][5][6] .…”
Section: High-throughput Single B Cell Sequencing Revealed Elevated S...mentioning
confidence: 99%
“…The recently emerged Omicron variant effectively evades most characterized antibodies 2 likely contributing to an increased rate of breakthrough infections 3 . Studies of antibody responses in naive individuals infected by the original SARS-CoV-2 strain revealed that germline-like antibodies are widely and rapidly induced [4][5][6] . Antibody isolation and informatics studies revealed that germline antibodies of different clonotypes preferentially target specific spike protein surfaces generating antibodies of 4 different classes as define by epitope locations 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Advances in high-throughput sequencing continue to improve our understanding of diseases, especially in the application of BCR repertoire ( Yaari and Kleinstein, 2015 ). In recent years, BCR repertoire sequencing has been reported to be applied to dozens of immune-mediated diseases, especially in systemic lupus erythematosus (SLE) ( Bashford-Rogers et al., 2019 ; Liu et al., 2017 ; Zheng et al., 2021 ), COVID-19 ( Bieberich et al., 2021 ; Galson et al., 2020 ; Jin et al., 2021 ; Montague et al., 2021 ; Niu et al., 2020 ; Paschold et al., 2021 ; Schultheiβ et al., 2020 ; Xiang et al., 2022 ; Zhang et al., 2020a , 2022 ; Zhou et al., 2021 ) and vaccination ( Lee et al., 2016a ; Miyasaka et al., 2019 ; Schneikart et al., 2020 ; Strauli and Hernandez, 2016 ; Zhao et al., 2021a , 2021b ). With the advent of bioinformatics and the development of a variety of bioinformatics analysis tools, we have grasped a more comprehensive understanding of diseases, and meanwhile, disease diagnosis and treatment have become increasingly diversified ( Liu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%